2021
DOI: 10.23937/2474-3690/1510063
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Hypertension and Its Associated Factors among Adult People Living in Southern Ethiopia: Evidence from Gunchire Woreda of Gurage Zone

Abstract: Background: Hypertension is defined as two or more readings of systolic blood pressure measurement of 130 mmHg or higher or diastolic blood pressure measurement of 80 mmHg or higher. In the early stages, symptoms of hypertension (HTN) are often not detectable and thus many people with the disease are left undiagnosed. Undiagnosed HTN increases the risk of complications such as renal failure, myocardial infarction, heart failure, stroke and premature death. There is paucity of data concerning undiagnosed hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
3
8
1
Order By: Relevance
“…Finally, this study finding showed that participants who had alcohol drinking experience were significantly associated with hypertension. This finding agrees with studies done in Kenya [ 32 ], and Eastern Ethiopia, Jugal hospital [ 1 , 11 ]. This finding is also supported by clinical studies which stated that chronic alcohol consumption of more than three drinks per day contributes to the incidence of hypertension [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Finally, this study finding showed that participants who had alcohol drinking experience were significantly associated with hypertension. This finding agrees with studies done in Kenya [ 32 ], and Eastern Ethiopia, Jugal hospital [ 1 , 11 ]. This finding is also supported by clinical studies which stated that chronic alcohol consumption of more than three drinks per day contributes to the incidence of hypertension [ 8 ].…”
Section: Discussionsupporting
confidence: 93%
“… Hypertension : Is a high blood pressure having a systolic blood pressure (SBP) ≥ 130 mmHg or diastolic blood pressure (DPB) ≥ 80 mm Hg on at least two occasions [ 3 ]. Undiagnosed hypertension : Refers to individuals who were hypertensive but did not report having been told by a health professional that they have hypertension [ 1 ]. Comorbid disease : a chronic disease with a confirmed diagnosis of a disease other than hypertension [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations